Download presentation
Presentation is loading. Please wait.
1
Integration by Substitution
For some integrations involving a complicated expression, we can make a substitution to turn it into an equivalent integration that is simpler. We wouldnβt be able to use βreverse chain ruleβ on the following: Q Use the substitution π’=2π₯+5 to find π₯ 2π₯+5 ππ₯ The aim is to completely remove any reference to π₯, and replace it with π’. Weβll have to work out π₯ and ππ₯ so that we can replace them. STEP 1: Using substitution, work out π₯ and ππ₯ (or variant) ? ππ’ ππ₯ =2 β ππ₯= 1 2 ππ’ Bro Tip: Be careful about ensuring you reciprocate when rearranging. π₯= π’β5 2 π₯ 2π₯+5 ππ₯= π’β5 2 π’ 1 2 ππ’ = π’ π’β5 ππ’ = π’ β5 π’ 1 2 = π’ β π’ πΆ = 2π₯ β 5 2π₯ πΆ ? STEP 2: Substitute these into expression. Bro Tip: If you have a constant factor, factor it out of the integral. STEP 3: Integrate simplified expression. ? STEP 4: Write answer in terms of π₯. ?
2
How can we tell what substitution to use?
In Edexcel you will usually be given the substitution! However in some other exam boards, and in STEP, you often arenβt. Thereβs no hard and fast rule, but itβs often helpful to replace to replace expressions inside roots, powers or the denominator of a fraction. Sensible substitution: cos π₯ 1+ sin π₯ ππ₯ ? π=π+ π¬π’π§ π 6π₯ π π₯ 2 ππ₯ ? But this can be integrated by inspection. π= π π π₯ π π₯ 1+π₯ ππ₯ ? π=π+π π 1βπ₯ 1+π₯ ππ₯ π= πβπ π+π ?
3
Another Example Q Use the substitution π’= sin π₯ +1 to find cos π₯ sin π₯ 1+ sin π₯ ππ₯ STEP 1: Using substitution, work out π₯ and ππ₯ (or variant) ? π’= sin π₯ +1 ππ’ ππ₯ = cos π₯ β ππ’= cos π₯ ππ₯ sin π₯ =π’β1 Notice this time we didnβt find π or π
π. We could, but then π= ππ«ππ¬π’π§ (πβπ) , and it would be slightly awkward simplifying the expression (although is still very much a valid method!) STEP 2: Substitute these into expression. ? = π’β1 π’ 3 ππ’ = π’ 4 β π’ 3 ππ’ = 1 5 π’ 5 β 1 4 π’ 4 +πΆ = sin π₯ β sin π₯ πΆ STEP 3: Integrate simplified expression. ? STEP 4: Write answer in terms of π₯. ?
4
Using substitutions involving implicit differentiation
When a root is involved, it makes thing much tidier if we use π’ 2 =β¦ Q Use the substitution π’ 2 =2π₯+5 to find π₯ 2π₯+5 ππ₯ STEP 1: Using substitution, work out π₯ and ππ₯ (or variant) ? 2π’ ππ’ ππ₯ =2 β ππ₯=π’ ππ’ π₯= π’ 2 β5 2 π₯ 2π₯+5 ππ₯= π’ 2 β5 2 π’Γπ’ππ’ = π’ 4 β 5 2 π’ 2 ππ’ = π’ 5 β 5 6 π’ 3 +πΆ = 2π₯ β 5 2π₯ πΆ ? STEP 2: Substitute these into expression. STEP 3: Integrate simplified expression. ? STEP 4: Write answer in terms of π₯. ? This was marginally less tedious than when we used π’=2π₯+5, as we didnβt have fractional powers to deal with.
5
Test Your Understanding
Edexcel C4 Jan 2012 Q6c Hint: You might want to use your double angle formula first. ? ππ’ ππ₯ =β sin π₯ β ππ₯=β 1 sin π₯ ππ’ cos π₯ =π’β1 (As before π₯= arccos π’β1 is going to be messy) 2 sin 2π₯ 1+ cos π₯ ππ₯ = 4 sin π₯ cos π₯ 1+ cos π₯ ππ₯ = β 4 sin π₯ π’β1 π’ 1 sin π₯ ππ’ =β4 π’β1 π’ ππ’ =β4 1β 1 π’ ππ’ =β4 π’β ln π’ +π=β4 1+ cos π₯ β ln cos π₯ π=β¦
6
Definite Integration ? ? ? ? Now consider:
Q Calculate 0 π 2 cos π₯ 1+ sin π₯ ππ₯ ? Use substitution: π=π+ π¬π’π§ π ππ’ ππ₯ = cos π₯ β ππ’= cos π₯ ππ₯ sin π₯ =π’β1 Now because weβve changed from π to π, we have to work out what values of π would have given those limits for π: When π₯= π 2 , π’=2 When π₯=0, π’=1 0 π 2 cos π₯ 1+ sin π₯ ππ₯= 1 2 π’ ππ’ = π’ = β1 ? ? ?
7
Test Your Understanding
Edexcel C4 June 2011 Q4 ? π
π π
π =ππ β π
π=ππ π
π π π =πβπ When π= π , π= π π +π=π When π=π, π= π π +π=π π π π π π₯π§ π π +π π π
π= π π π π (πβπ) π₯π§ π π
π
8
Exercise 6F ? ? ? ? ? ? ? ? ? Use the given substitution to integrate.
Use an appropriate substitution. π₯ 1+π₯ ππ₯ ; π’=1+π₯ = π π π+π π π β π π π+π π π +πͺ sin π₯ cos π₯ ππ₯;π’= sin π₯ =β π₯π§ πβ π¬π’π§ π +πͺ sin 3 π₯ ππ₯ ; π’= cos π₯ = π π ππ¨π¬ π π β ππ¨π¬ π +πͺ π₯ 2+π₯ ππ₯ ; π’ 2 =2+π₯ = π π π+π π π β π π π+π π π +πͺ sec 2 π₯ tan π₯ 1+ tan π₯ ππ₯ ; π’ 2 =1+ tan π₯ = π π π+ πππ§ π π π β π π π+ πππ§ π π π +πͺ sec 4 π₯ ππ₯ ; π’= tan π₯ = πππ§ π + π π πππ§ π π +πͺ 1 a 0 5 π₯ π₯+4 ππ₯ = πππ ππ π₯β1 ππ₯ =π+π π₯π§ π π 0 1 π₯ 2+π₯ 3 ππ₯ =π.π ? 3 a ? c c ? ? e ? e ? 2 a ? c ? e ?
9
Integration by Parts Proof ? π₯ cos π₯ ππ₯ =? ! To integrate by parts:
Just as the Product Rule was used to differentiate the product of two expressions, we can often use βIntegration by Partsβ to integrate a product. ! To integrate by parts: π’ ππ£ ππ₯ ππ₯=π’π£β π£ ππ’ ππ₯ ππ₯ Proof ? (not needed for exam) The Product Rule: π ππ₯ π’π£ =π£ ππ’ ππ₯ +π’ ππ£ ππ₯ On the right-hand-side, both π£ ππ’ ππ₯ and π’ ππ£ ππ₯ are the product of two expressions. So if we made either the subject, we could use π’ ππ£ ππ₯ say to represent π₯ cos π₯ in the example. Rearranging: π’ ππ£ ππ₯ = π ππ₯ π’π£ βπ£ ππ’ ππ₯ Integrating both sides with respect to π₯, we get the desired formula.
10
Integration by Parts ? ? ? π’ ππ£ ππ₯ ππ₯=π’π£β π£ ππ’ ππ₯ ππ₯ π₯ cos π₯ ππ₯ =?
π’ ππ£ ππ₯ ππ₯=π’π£β π£ ππ’ ππ₯ ππ₯ π₯ cos π₯ ππ₯ =? ? π’=π₯ ππ£ ππ₯ = cos π₯ ππ’ ππ₯ = π£= sin π₯ π₯ cos π₯ ππ₯ =π₯ sin π₯ β 1 sin π₯ ππ₯ =π₯ sin π₯ + cos π₯ +πΆ STEP 1: Decide which thing will be π’ (and which ππ£ ππ₯ ). Youβre about to differentiate π’ and integrate ππ£ ππ₯ , so the idea is to pick them so differentiating π’ makes it βsimplerβ, and ππ£ ππ₯ can be integrated easily. π’ will always be the π₯ π term UNLESS one term is ln π₯ . ? STEP 2: Find ππ’ ππ₯ and π£. STEP 3: Use the formula. ? I just remember it as βπ’π£ minus the integral of the two new things timesed togetherβ
11
Another Example ? Find π₯ 2 ln π₯ ππ₯ Q π’= ln π₯ ππ£ ππ₯ = π₯ 2
ππ’ ππ₯ = 1 π₯ π£= 1 3 π₯ 3 π₯ 2 ln π₯ ππ₯ = 1 3 π₯ 3 ln π₯ β π₯ 2 ππ₯ = π π π π π₯π§ π β π π π π +πͺ This time, we choose ln π₯ to be the π’ because it differentiates nicely. STEP 1: Decide which thing will be π’ (and which ππ£ ππ₯ ). STEP 2: Find ππ’ ππ₯ and π£. STEP 3: Use the formula.
12
IBP twice! ο Q Find π₯ 2 π π₯ ππ₯ ? π’= π₯ ππ£ ππ₯ = π π₯ ππ’ ππ₯ =2π₯ π£= π π₯ π₯ 2 π π₯ ππ₯ = π₯ 2 π π₯ β 2π₯ π π₯ ππ₯ We have to apply IBP again! π’=2π₯ ππ£ ππ₯ = π π₯ ππ’ ππ₯ = π£= π π₯ 2π₯ π π₯ ππ₯ =2π₯ π π₯ β 2 π π₯ ππ₯ =2π₯ π π₯ β2 π π₯ Therefore π₯ 2 π π₯ ππ₯ = π₯ 2 π π₯ β 2π₯ π π₯ β2π₯ π π₯ +πΆ = π₯ 2 π π₯ β2π₯ π π₯ +2 π π₯ +πΆ Bro Tip: I tend to write out my working for any second integral completely separately, and then put the result back into the original integral later.
13
Test Your Understanding
Q Find π₯ 2 sin π₯ ππ₯ ? =2π₯ sin π₯ β π₯ 2 cos π₯ +2 cos π₯ +πΆ
14
Integrating ln π₯ and definite integration
Q Find ln π₯ ππ₯ , leaving your answer in terms of natural logarithms. π’= ln π₯ ππ£ ππ₯ =1 ππ’ ππ₯ = 1 π₯ π£=π₯ ln π₯ ππ₯ =π₯ ln π₯ β 1 ππ₯ =π₯ ln π₯ βπ₯+πΆ ? Q Find ln π₯ ππ₯ , leaving your answer in terms of natural logarithms. 1 2 ln π₯ ππ₯ = π₯ ln π₯ βπ₯ 1 2 =π π₯π§ π βπ If we were doing it from scratch: π’= ln π₯ ππ£ ππ₯ =1 ππ’ ππ₯ = 1 π₯ π£=π₯ ln π₯ ππ₯ = π ππ π π π β ππ₯ =2 ln 2 β1 ln 1 β π₯ =2 ln 2 β(2β1) =2 ln 2 β1 ? In general: π π π’ ππ£ ππ₯ ππ₯ = π’π£ π π β π π π£ ππ’ ππ₯ ππ₯
15
Test Your Understanding
Q Find 0 π 2 π₯ sin π₯ ππ₯ ? π’=π₯ ππ£ ππ₯ = sin π₯ ππ’ ππ₯ = π£=β cos π₯ π₯ sin π₯ ππ₯ =βπ₯ cos π₯ β β cos π₯ ππ₯ =βπ₯ cos π₯ + cos π₯ ππ₯ =βπ₯ cos π₯ + sin π₯ ππ₯ β΄ 0 π 2 π₯ sin π₯ ππ₯ = βπ₯ cos π₯ + sin π₯ 0 π 2 = β π 2 cos π 2 + sin π 2 β 0+ sin 0 =1
16
Exercise 6G ? ? ? ? ? ? ? ? ? ? ? ? ? ? 1 3 a a c c e 4 a e c 2 e a g
π₯ 2 π βπ₯ ππ₯=β π βπ π π βππ π βπ βπ π βπ +πͺ 12 π₯ π₯ 5 ππ₯ = π π π+ππ π β π π π π+ππ π + π πππ π+ππ π +πͺ π₯ 2 2 sec 2 π₯ tan π₯ ππ₯ = π π π¬ππ π π βππ πππ§ π +π π₯π§ π¬ππ π +πͺ 0 ln 2 π₯ π 2π₯ ππ₯=π π₯π§ π β π π 0 π 2 π₯ cos π₯ ππ₯ = π
π βπ 0 1 4π₯ 1+π₯ 3 ππ₯=π.π 0 π 3 sin π₯ lnβ‘( sec π₯) ππ₯ = π π πβ π₯π§ π π₯ sin π₯ ππ₯ =βπ ππ¨π¬ π + π¬π’π§ π +πͺ π₯ sec 2 π₯ ππ₯ =π πππ§ π β π₯π§ π¬ππ π +πͺ π₯ sin 2 π₯ ππ₯ =βπ ππ¨π π + π₯π§ π¬π’π§ π +πͺ π₯ 2 ln π₯ ππ₯ = π π π π π₯π§ π β π π π π +πͺ ln π₯ π₯ 3 ππ₯ =β π₯π§ π π π π β π π π π +πͺ π₯ ln π₯ ππ₯ = π π π π π₯π§ π β π π π π +π π₯π§ π βπ 3 a ? a ? c ? ? c e ? 4 ? a Bonus Question: arcsin π₯ ππ₯ = πβ π π +π ππ«ππ¬π’π§ π +πͺ (hint: ππ£ ππ₯ =1) e ? ? c ? ? ? 2 e a ? ? g c ? You will need the following standard results (given in your formula booklet). Weβll prove them later. ! tan π₯ ππ₯ = ln sec π₯ +πΆ sec π₯ ππ₯ = ln sec π₯+ tan π₯ +πΆ cot π₯ ππ₯ = ln sππ π₯ +πΆ cosec π₯ ππ₯ = ln cosec π₯+ cot π₯ +πΆ e
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.